1998
DOI: 10.1046/j.1365-2435.1998.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced thermotolerance and associated expression of the heat‐shock protein Hsp70 in adult Drosophila melanogaster

Abstract: 1. Inducible heat‐shock proteins are synthesized when temperatures are increased to levels substantially above normal. The functional role of these proteins is well known at the cellular level. Today increasing interest has been directed towards the importance of heat‐shock proteins for resistance of whole organisms to high‐temperature stress and other environmental stressors. 2. Here the functional relationship between the heat‐shock protein, Hsp70, and thermal resistance in adult Drosophila melanogaster was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
177
3
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(196 citation statements)
references
References 27 publications
11
177
3
3
Order By: Relevance
“…Several studies have found a positive correlation between heat tolerance and HSP70 expression (Bahrndorff et al, 2009), whereas others have shown opposite or no correlations (Dahlgaard et al, 1998;Bahrndorff et al, 2009Bahrndorff et al, , 2010. Using the same treatments as herein a previous study on B. anynana, we showed that exposure for 2 h to 39 1C strongly increased subsequent heat-stress survival (Franke and Fischer, 2013), suggesting that a positive relationship between HSP70 expression and heat tolerance exists also in our study organism.…”
Section: Discussionsupporting
confidence: 76%
“…Several studies have found a positive correlation between heat tolerance and HSP70 expression (Bahrndorff et al, 2009), whereas others have shown opposite or no correlations (Dahlgaard et al, 1998;Bahrndorff et al, 2009Bahrndorff et al, , 2010. Using the same treatments as herein a previous study on B. anynana, we showed that exposure for 2 h to 39 1C strongly increased subsequent heat-stress survival (Franke and Fischer, 2013), suggesting that a positive relationship between HSP70 expression and heat tolerance exists also in our study organism.…”
Section: Discussionsupporting
confidence: 76%
“…This is in contrast to a previous study on a mid-intertidal limpet, Cellana toreuma, that found no Hsp70 response to aerial exposure alone at 20 °C (Huang et al 2015). Although there is an accumulating body of evidence that suggests that the heat-shock response and the induction of Hsps is a primary cellular mechanism underlying heat hardening (Kregel 2002;Sørensen et al 2003), several studies have found that heat hardening may be uncoupled with Hsp synthesis and concentrations (Easton et al 1987;Dahlgaard et al 1998). In the current study, Ub-conjugated proteins were measured directly as a measure of protein damage present in the limpets prior to exposure to the lethal temperature increase.…”
Section: Inducible Thermal Tolerancecontrasting
confidence: 74%
“…The structure of Hsp70 is phylogenetically highly conserved, even though the capacities for its induction may vary considerably among populations of the same species (Köhler et al 2000). Differences in Hsp70 levels can directly account for stress tolerance (Köhler et al 1992;Dahlgaard et al 1998;Feder and Hofmann 1999;Köhler et al 2000), which often is influenced by microgeographical selection processes. Since the production of stress proteins, however, is energy consuming, it is reasonable to assume that Hsp induction trades off against other fitness parameters because of constraints in energy allocation (Krebs and Loeschcke 1994;Silbermann and Tatar 2000;Kristensen et al 2008).…”
Section: Introductionmentioning
confidence: 99%